Assessment of the efficiency of image analyzer applications in determining substrate quality for vegetable seedling development - Michels, Roger Nabeyama; Dal Bosco, Tatiane Cristina; Chennecdge Vieira, Murilo (Brazilian Journal of Biometrics, 2024)
The aim of this study is to evaluate the efficiency of images analyzer applications in determining substrate quality for vegetable seedling development. Two leaf coverage determiner apps using digital images, Canopeo and GreenTest, were tested and their values were compared with results obtained from NDVI, fresh mass, dry mass, and humidity in a substrate testing experiment for lettuce seedling development. The experiment, employing a completely redomized design with 4 treatments (control, witness, humus and organic compost) and 4 repetitions, took place in a greenhouse in Londrina, Paraná, Brazil, in April 2022. Results indicated that the Canopeo app demonstrated greater sensitivity in distinguishing between treatments and exhibited a very strong correlation with other scientifically employed analyses. In contrast, GreenTest showed moderate correlation and lower sensitivity in the analyses. In conclusion, Canopeo proves to be a reliable application for determining leaf coverage and analyzing the performance of vegetable seedlings.